2014
DOI: 10.1021/bc5003423
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Conjugation: Before or After Nanoparticle Formation?

Abstract: We report herein a detailed study concerning the impact of different bioconjugation and nanoformulation strategies on the in vitro targeting ability of peptide-decorated squalenoyl gemcitabine (SQdFdC) nanoparticles (NPs). NPs have been functionalized with the CKAAKN peptide, previously identified as efficient homing device within the pancreatic pathological microenvironment. Two approaches have been followed: (i) either the CKAAKN peptide was directly conjugated at the surface of preformed SQdFdC nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 55 publications
0
39
0
Order By: Relevance
“…In another study, SQ–GEM was decorated with SQ conjugated targeting peptide CKAAN through coprecipitation. 49,103 The nanoassemblies with CKAAN showed a higher specificity in cellular uptake and cytotoxicity in Paca-2 pancreatic cancer cells. 103 In a separate study, a technology called lipocore was developed.…”
Section: Delivery Systems For Lipid–drug Conjugatementioning
confidence: 99%
“…In another study, SQ–GEM was decorated with SQ conjugated targeting peptide CKAAN through coprecipitation. 49,103 The nanoassemblies with CKAAN showed a higher specificity in cellular uptake and cytotoxicity in Paca-2 pancreatic cancer cells. 103 In a separate study, a technology called lipocore was developed.…”
Section: Delivery Systems For Lipid–drug Conjugatementioning
confidence: 99%
“…In contrast, in the case of ligand-modified liposomes prepared by the postinsertion method, all of the ligands are facing outward from the membrane but ligand-modified micelles also remain in the reaction solution. [21][22][23] Because the modified micelles have the ability to bind to targeting receptors, it is important to determine the purity of the liposomes, and to evaluate the density of surface ligands, [24][25][26][27][28] which serve as an index of the quality of the liposomes. [29][30][31][32] Surface reaction modification can efficiently modify the liposomal surface without micelle contamination, and ensures that the ligands are orientated facing outward from the membrane.…”
Section: -9)mentioning
confidence: 99%
“…SQGem NPs have been decorated with the CKAAKN peptide for selective targeting of pancreatic cancer cells. 167 In vivo studies on RipTag2 mice, a model of spontaneously arising islet cell carcinoma, revealed the superior efficacy of the peptidedecorated nanoparticles compared with their non-functionalized counterpart. 168 Altogether, these data clearly demonstrated that the squalenoylation approach is a powerful tool for overcoming the impaired uptake of gemcitabine caused by NT-mediated resistance.…”
Section: Impaired Drug Uptakementioning
confidence: 99%